2021
DOI: 10.3390/rs13183679
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Permittivity Estimation of Lunar Regolith Using the Lunar Penetrating Radar Onboard Chang’E-4 Rover

Abstract: Accurate relative permittivity is essential to the further analysis of lunar regolith. The traditional hyperbola fitting method for the relative permittivity estimation using the lunar penetrating radar generally ignored the effect of the position and geometry of antennas. This paper proposed a new approach considering the antenna mounting height and spacing in more detail. The proposed method is verified by numerical simulations of the regolith models. Hence the relative permittivity of the lunar regolith is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 41 publications
(81 reference statements)
1
25
0
Order By: Relevance
“…The model is 10 m in length, and 11 m in depth, and the spatial steps in the X (length) and Y (depth) direction are both 0.005 m. The time window is 150 ns, the time step is 0.0118 ns. The moving steps of both transmitter and receiver antenna are 0.05 m. The average permittivity of background material is 3.5, which is consistent with the result of Lai et al [13] and Wang et al [15]. The relative loss tangent is set as 0.02, which indicates the average conductivity of the model is about 2 × 10 −3 (e.g., Figure 3b).…”
Section: Simulation Modelsupporting
confidence: 82%
See 2 more Smart Citations
“…The model is 10 m in length, and 11 m in depth, and the spatial steps in the X (length) and Y (depth) direction are both 0.005 m. The time window is 150 ns, the time step is 0.0118 ns. The moving steps of both transmitter and receiver antenna are 0.05 m. The average permittivity of background material is 3.5, which is consistent with the result of Lai et al [13] and Wang et al [15]. The relative loss tangent is set as 0.02, which indicates the average conductivity of the model is about 2 × 10 −3 (e.g., Figure 3b).…”
Section: Simulation Modelsupporting
confidence: 82%
“…Furthermore, Lai et al (2020) used the impact crater ejecta empirical model to estimate the ejecta thickness of the Finsen Crater in the Chang'e-4 landing site to be 7.9 meters, close to the thickness of the lunar regolith based on the radar observation [12]. In summary, recent research showed that there is a 12 m-thick fine regolith layer under the Yutu-2 rover's motion path, and most of surficial materials came from the Finsen Crater [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, the thickness of the regolith is unevenly distributed over the whole Moon [44]. Two high-precision in-situ radars measurement on the Moon suggest that the thickness of regolith is >10 m, e.g., Chang'E-3 and Chang'E-4 sites [26], [67], [68], [69], indicating that the global thickness of regolith is likely to be underestimated.…”
Section: Space Policy Feasibilitymentioning
confidence: 99%
“…1). Although hyperbola fitting can be modified to address non-flat surfaces [18] and air-coupled antennas [19], nonetheless, the scenario mentioned above is the most typical and mainstream case study under consideration. Hyperbola fitting only utilises the shape of the hyperbola, meaning that it is amplitudeagnostic.…”
Section: Hyperbola Fittingmentioning
confidence: 99%